Physical and Psychological Stressor Exposure during Pregnancy Impacts the Expression of Synapsin and Neuronal Cells Number of MUS Musculus Offspring - Diana Estu Rumahastuti; Hermanto Tri Joewono; Widjiati (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: Stress during gestation can lead to inappropriate fetal brain development, especiallypsychological stress. Psychological stress play pivotal role in offsprings’ brain development.Objective: The aim of this study was to investigate the effects of maternal exposure to physical andpsychological stress during pregnancy on the cerebrum in mice offspring.Method: This study was an analytical experiment study with the subject were 24 female mice Musmusculus. The sample were divided into treatment and control group. Treatment groups divided intothree conditions, 1 group was given physical stress, 1 group with psychological stress, and 1 groupwas given combination of physical and psychological stress intervention. The data were analyzed withANOVA test then followed by LSD to find the differences between all groups.Results: The ANNOVA test results showed significant differences of the expression of synapsin withp = 0.0000. The number of neuronal cells also represented significant differences with p = 0.000 on thecerebrum.Conclusion: Stress exposure during pregnancy can induce bad impacts in brain development, especiallythe expression of synapsin and the number of neuronal cells on the cerebrum in mice offspring.